Risk factors of neonatal hypoglycemia - Yuliana Yunarto; Gatot Irawan Sarosa (Paediatrica Indonesiana, 2019)
Background Hypoglycemia is the most common metabolic issue in newborns and should be treated as soon as possible to prevent complications of neurologic impairment, mental retardation, developmental delay, and cardiovascular disorders. Objective To assess maternal, fetal, and neonatal factors for identifying infants at risk of developing neonatal hypoglycemia. Methods This case-control study was conducted in the Perinatal Unit of Dr. Kariadi Hospital, Semarang, Central Java. A total of 123 newborns with blood glucose <47 mg/dL comprised the case group and 123 newborns without hypoglycemia comprised the control group. Characteristics of infants, maternal age, maternal pregnancy-related conditions, as well as fetal and neonatal factors were recorded and analyzed for possible relationships with hypoglycemia. Results Out of 677 newborns, hypoglycemia was found in 123 (18.2%) infants (59 male, 64 female). In the case group, 58 (47.1%) were preterm, 38 (30.9%) very preterm, and 8 (6.5%) extremely preterm infants. Factors associated with neonatal hypoglycemia were prematurity (OR 6.537; 95%CI 3.543 to 12.063; P <0.001), low birth weight (OR 2.979; 95% CI 1.532 to 5.795; P<0.001), small for gestational age (OR 1.805; 95% CI 1.054 to 3.095; P=0.031), and birth asphyxia(OR 3.386; 95% CI 1.945 to 5.895; P<0.001). In multivariate regression analysis, prematurity and low birth weight remained the significant factors associated with neonatal hypoglycemia. Conclusion Prematurity and low birth weight are significant risk factors associated with neonatal hypoglycemia. Routine screening and monitoring of blood glucose is recommended for preterm newborns and infants with low birth weight